Neutron Applications in Materials for Energy - Kearley, Gordon J.; Peterson, Vanessa K. (Neutron Scattering Applications and Techniques, 2015)
This book collects the results and conclusions of recent neutron-based investigations of materials that are important in the development of sustainable energy. The individual chapters were written by leading scientists with hands-on experience in the field, providing overviews, recent highlights, and case studies to illustrate the applicability of one or more neutron-based analytical techniques. Though the main focus is on energy production, storage, and use, each chapter and section can also be read independently, with basic theory and instrumentation for neutron scattering being outlined in the introductory chapter. While neutron scattering is extensively used to understand the properties of condensed matter, neutron techniques are exceptionally-well suited to studying how the transport and binding of energy and charge-carrying molecules and ions are related to their dynamics and the material's crystal structure. In some cases, these studies extend to in situ and in operando. The species of interest in leading energy-technologies include H2, H+, and Li+, as their particularly favorable neutron-scattering properties make them ideal for such studies; as a result, neutron-based analysis is commonplace for hydrogen storage, fuel-cell, catalytic, and battery materials. Similar research into the functionality of solar-cell, nuclear, and CO2 capture/storage materials rely on other unique aspects of neutron scattering and again show how their structure and dynamics provide an understanding of the material stability and the binding and mobility of species of interest. Scientists and students looking for methods to help them understand the atomic-level mechanisms and behavior underpinning the performance characteristics of energy materials will find Neutron Applications in Materials for Energy a valuable resource, while the broader audience of sustainable energy scientists and newcomers to neutron scattering should find this a valuable reference work.